Design and Experimental Study of Hydrogen Elimination Device for Pd / Pt Exhaust Gas of Proton Exchange Membrane Fuel Cell - Zhang Dahe; Yuan Kun; Xu Zishun; Lin Weikang; Ma Tiancai (E3S Web of Conferences, 2024)
This study addresses incomplete hydrogen emissions from hydrogen fuel cell exhausts, focusing on developing safe, efficient strategies to reduce residual hydrogen levels, ensuring compliance with strict environmental and safety norms. Despite maximizing hydrogen utilization, fuel cells inevitably emit residual hydrogen, posing safety risks. An innovative exhaust hydrogen eliminator design is proposed, examining the efficacy of a palladium/platinum catalyst in enhancing hydrogen removal via catalytic combustion. Through systematic investigation on a specialized test platform, factors like airflow, temperature, pressure, and hydrogen concentration influenced the catalytic hydrogen eliminator’s performance. Results highlight the palladium/platinum catalyst’s impact on hydrogen conversion, notably superior platinum performance over palladium, achieving maximum elimination rates of 61% and 96%, respectively. Catalyst shell temperature correlated with input hydrogen concentration, stabilizing near 102°C at 1.97% hydrogen, indicating stable catalytic reactions under tested conditions, pivotal for low-temperature combustion within the hydrogen eliminator.